From Public Mental Health to Community Oral Health: The Impact of Dental Anxiety and Fear on Dental Status - Crego, Antonio; Carrillo, María; Armfield, Jason M.; Romero, Martin (Frontiers in Public Health, 2014)
Dental fear is a widely experienced problem. Through a “vicious cycle dynamic,” fear of dental treatment, lower use of dental services, and oral health diseases reinforce each other. Research on the antecedents of dental anxiety could help to break this cycle, providing useful knowledge to design effective community programs aimed at preventing dental fear and its oral health-related consequences. In this regard, frameworks that analyze the interplay between cognitive and psychosocial determinants of fear, such as the Cognitive Vulnerability Model, are promising. The onset of dental fear often occurs in childhood, so focusing on the child population could greatly contribute to understanding dental fear mechanisms and prevent this problem extending into adulthood. Not only can public mental health contribute to population health, but also community dentistry programs can help to prevent dental fear. Regular dental visits seem to act in a prophylactic way, with dental professionals playing an important role in the regulation of the patients’ anxiety-related responses. Both public mental health and community dentistry could therefore benefit from a multidisciplinary approach to dental fear and oral health.